Discovering the most elusive radio relic in the sky: diffuse shock acceleration caught in the act?. (7th May 2020) - Locatelli, Nicola T; Rajpurohit, Kamlesh; Vazza, Franco; Gastaldello, Fabio; Dallacasa, Daniele; Bonafede, Annalisa; Rossetti, Mariachiara; Stuardi, Chiara; Bonassieux, Etienne; Brunetti, Gianfranco; Brüggen, Marcus; Shimwell, Timothy
ABSTRACT: The origin of radio relics is usually explained via diffusive shock acceleration (DSA) or re-acceleration of electrons at/from merger shocks in galaxy clusters. The case of acceleration is challenged by the low predicted efficiency of low Mach number merger shocks, unable to explain the power observed in most radio relics. In this letter, we present the discovery of a new giant radio relic around the galaxy cluster Abell 2249 (z = 0.0838) using Low-Frequency Array (LOFAR). It is special since it has the lowest surface brightness of all known radio relics. We study its radio and X-ray properties combining LOFAR data with uGMRT, JVLA, and XMM . This object has a total power of L_1.4 GHz=4.1± 0.8 × 10^23 W Hz −1 and integrated spectral index α = 1.15 ± 0.23. We infer for this radio relic a lower bound on the magnetization of B0.4 μ G, a shock Mach number of M≈ 3.79, and a low acceleration efficiency consistent with DSA. This result suggests that a missing population of relics may become visible, thanks to the unprecedented sensitivity of the new generation of radio telescopes.